The Effect of Bank’s Performance on Return on Asset - Hutasoit, SE., MSi., MSE, Posma Sariguna Johnson Kennedy; Agustina, Doan Otanti (Universitas Kristen Indonesia, 2016)
This study aims to determine the performance of banks in Indonesia and their return on assets (ROA), and to know the problems faced by a bank in connection with the banking performance. The data used in this research is secondary data. Data in the form of financial ratios processed by Research Bureau of the bank's financial statements as of December 2008-2014 that has been audited and published in the June issue of InfoBank 2015. The method used in this research is quantitative method. Classic assumption test used in this study include normality, multicollinearity, heteroskedatisitas, autocorrelation and regression models. The conclusion that can be drawn, ROA is affected by the six independent variable: CAR, NPL, LDR, ROA and NIM. Based on the regression equation shown that the variable CAR partially no effect on ROA. NIM variable is positive influenced, so it can be interpreted that the influence exerted by variables NIM to ROA is positive.Keywords : Return on Asset, Capital Adequacy Ratio, Net Interest Margin,Non Performing Loan, Loan to Deposit Ratio.